Evaluation of the safety and efficacy of transarterial sevelamer embolization in a rabbit liver cancer model: A challenge on the size rule for vascular occlusion - Chen, Hong; Xie, Chuan-Sheng; Li, Yan-Shu; Deng, Zhi-Qiang; Lv, Yang-Feng; Bi, Qiu-Chen; Tang, Jian-Jun; Luo, Rong-Guang; Tang, Qun (Frontiers in Bioengineering and Biotechnology, 2022)
As the most efficient method to treat hepatocellular carcinoma in the immediate or advanced stage, transarterial chemoembolization (TACE) is coming into the era of microsphere (MP). Drug-eluting beads have shown their huge potential as an embolic agent and drug carrier for chemoembolization, but their sizes are strictly limited to be above 40 µm, which was considered to occlude vessels in a safe mode. MP smaller than 40 µm is easy to be washed out and transported to normal liver lobe or other organs, causing severe adverse events and failed embolization. To determine whether sevelamer ultrafine particle (0.2-0.5 µm) is qualified as a safe and efficient embolic agent, we investigated the safety and therapeutic efficiency of transarterial sevelamer embolization (TASE) in the VX2 rabbit liver cancer model, aiming to challenge the “40 µm” rule on the selection criteria of the MP. In a four-arm study, blank bead (Callisphere, 100-300 µm), luminescent polystyrene microsphere (10, 100 µm), and sevelamer particle were transarterially administered to evaluate the threshold size of the MP size for intrahepatic or extrahepatic permeability. Another four-arm study was designed to clarify the safety and efficiency of preclinical TASE tests over other techniques. Sham (saline), TASE, C-TACE, and D-TACE (n=6) were compared in terms of serum chemistry, histopathology, and tumor necrosis ratio. In the first trials, the “40 µm” rule was detectable on the VX2 cancer model, but the regulation has no application to the new embolic agent as sevelamer ultrafine particles have not been found to leak out from the VX2 lesions, only found in the embolized vessels. Pathology proves that less viable tumor residue was found 2 weeks after the procedure, evidencing a better therapeutic outcome. No adverse events were found except a short stress response. These results indicate that sevelamer is a safe and efficient embolic as an alternative to the current MP-based embolization therapy techniques.